2019
DOI: 10.1074/jbc.ra118.005621
|View full text |Cite
|
Sign up to set email alerts
|

The RING domain in the anti-apoptotic protein XIAP stabilizes c-Myc protein and preserves anchorage-independent growth of bladder cancer cells

Abstract: Edited by Eric R. Fearon X-linkedinhibitorofapoptosisprotein(XIAP)suppressesapoptosis and plays key roles in the development, growth, migration, and invasion of cancer cells. Therefore, XIAP has recently attracted much attention as a potential antineoplastic therapeutic target, requiring elucidation of the molecular mechanisms underlying its biological activities. Here, using shRNA-mediated gene silencing, immunoblotting, quantitative RT-PCR, anchorage-independent growth assay, and invasive assay, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It is generally acknowledged that the stability of the MYC protein is tightly associated with Thr58 and Ser62. 36 , 37 , 38 Ser62 phosphorylation is required for MYC stabilization, while Thr58 phosphorylation, which depends on prior Ser62 phosphorylation, is associated with MYC degradation. 39 However, few studies have investigated the tyrosine phosphorylation of MYC.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally acknowledged that the stability of the MYC protein is tightly associated with Thr58 and Ser62. 36 , 37 , 38 Ser62 phosphorylation is required for MYC stabilization, while Thr58 phosphorylation, which depends on prior Ser62 phosphorylation, is associated with MYC degradation. 39 However, few studies have investigated the tyrosine phosphorylation of MYC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that HA/CD44-mediated PKC signaling regulates the stem cell marker (Nanog)associated miR-21 production, which in turn down-regulates the tumor suppressor protein (PDCD4) and promotes oncogenesis, leading to survivin, X-linked inhibitor of apoptosis protein (XIAP) and MDR1 expression. Survivin, XIAP and MDR1 play key roles in cell survival, expansion, and migration [20]. In this study we focused on whether HA-CD44 interaction regulates RPCs migration via PKC/Nanog/miR-21 signaling.…”
Section: Rpcs Express Cd44 In Vitromentioning
confidence: 99%
“…Basic helix-loop-helix (bHLH) transcription factors are key factors in regulating lineage and development-specific gene networks. The bHLH proteins play an important role in a variety of biological processes by controlling the expression of genes related to proliferation [5], apoptosis [6], differentiation [7], autophagy [8], cell cycle [9], cell growth [10], development [11], angiogenesis [12], hematopoiesis [13], and morphogenesis [14]. Therefore, they are closely related to human health.…”
Section: Introductionmentioning
confidence: 99%